The influence of sunni islamic values on rehabilitation as judicial decision for minor drug users in Indonesian court - Cecep Mustafa (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
This article illustrates how recent research uses qualitative semi- structured interviews to understand judicial perceptions when convicting minor drug offenders. To develop an understanding of what the judges were trying to achieve when convicting drug offenders, I interviewed 31 judges. This article contributes to the sociol-legal understanding of the context in which problem- solving and justice influenced by Islamic religious values work in harmony. Indonesian judges use Islamic values to support rehabilitation. This supportive approach opens the door to the influence of Sunni Islamic values as one of the legitimating values when deciding.